QUALITY OF 95-WEEK-OLD ISA BROWN CHICKEN EGGS GIVEN COMMERCIAL RATIONS WITH ADDITIONAL SHELLS AS CALCIUM SOURCES - N. W. A., Ningsih; Dewi, G. A. M. K.; Wijana, I W. (Jurnal Peternakan Tropika, 2020)
This study aims to determine the quality of 95-week-old Isa Brown chicken eggs fed commercial rations with the addition of clam shells as a source of calcium. The study was conducted for 4 weeks in Pesedahan Village, Manggis District, Karangasem Regency, Bali and continued with sample analysis at the Poultry Laboratory of the Faculty of Animal Husbandry, Udayana University. The design used completely randomized design (CRD) consisted of 4 treatments and 5 replications where each repetition consisted of 5 chickens. The treatments given are chicken given commercial ration (P0), chicken given commercial ration plus 1% shells (P1), chicken given commercial ration plus 2% grit shells (P2) and chicken given commercial ration plus 3% grit conch shells (P3). Variables observed included egg weight, egg index, egg shell thickness, egg shell weight, egg yolk color, egg pH and Haugh Unit. The results showed that the provision of commercial rations with the addition of 1%, 2% and 3% shellfish grits as a source of calcium can produce egg weight, egg index, egg shell thickness, egg shell weight, egg yolk color, egg pH and different egg HaughUnit not significantly (P> 0.05) than chickens that were given commercial rations (P0). Based on the results of the study it can be concluded that the provision of commercial rations with the addition of clam shell grits as a source of calcium can not increase egg weight, egg index, egg shell thickness, egg shell weight, egg yolk color pH and Haugh Unit. Keywords: calcium, conch shell grits, isa brown, eggs